2012
DOI: 10.1063/1.3682781
|View full text |Cite
|
Sign up to set email alerts
|

Activation of water on the TiO2 (110) surface: The case of Ti adatoms

Abstract: Using first-principles calculations we have studied the reactions of water over Ti adatoms on the (110) surface of rutile TiO 2 . Our results provide fundamental insights into the microscopic mechanisms that drive this reaction at the atomic level and assess the possibility of using this system to activate the water dissociation reaction. In particular, we show that a single water molecule dissociates exothermically with a small energy barrier of 0.17 eV. After dissociation, both H + and OH − ions bind strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…By analysing the interaction of molecule on the three adsorption sites, surprisingly, it was found that binding of with Ti-6c ( eV) is energetically preferred over under-coordinated Ti-5c ( eV) and Ti-4c sites ( eV). This result is contrary to the adsorption on surfaces [ 39 ]. On crystalline surfaces water prefers to adsorb on under-coordinated site.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…By analysing the interaction of molecule on the three adsorption sites, surprisingly, it was found that binding of with Ti-6c ( eV) is energetically preferred over under-coordinated Ti-5c ( eV) and Ti-4c sites ( eV). This result is contrary to the adsorption on surfaces [ 39 ]. On crystalline surfaces water prefers to adsorb on under-coordinated site.…”
Section: Resultsmentioning
confidence: 72%
“…The reaction path was found to have similar TSs for both Fe(II)- (Figure 7 ), and rutile (1 1 0) (Figure 8 ) surfaces [ 39 ], where the molecule gets distorted resulting in elongated OH–H bond. However, for pristine surface TS consists of dissociated molecule with OH and H group bonded to the surface Ti and O atoms, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For the first reaction pathway in Fig. 4a for H 2 O splitting to OH and H, the H 2 O remains nearly intact with only small changes from the initial to the transition state, leading to a small energy barrier of only 0.02 eV, and a large exothermic energy of 2.46 eV to form the products OH and H. As is the case for Ti/C 60 4 and Ti/TiO 2 , 24 the O-H distance is slightly longer than the other one (1.05 Å vs. 0.98 Å) at the transition state and the longer one breaks subsequently. At the final state, the O of OH bonds to two Ti atoms and the bond length of Ti-H is 1.86 Å.…”
Section: Dissociation Of H 2 O On Ti 4 Cluster Embedded Graphenementioning
confidence: 84%
“…These paths may even have energy barriers closer to the splitting of water in other systems, where the energy barriers are as low as ∼0.1 eV. [45][46][47][48] However, a comprehensive ab initio sampling of larger clusters is prohibitively expensive. But, our main goal is not to find such paths or ways to dissociate water in MOF-74 in the most efficient manner.…”
Section: Barrier To Water Dissociationmentioning
confidence: 99%